The Urgency of Expert Witnesses in Settlement of Cases in The Egyptian Judicial Legal System - Ibrahim Munib; Muhammad Hasyied Abdurrasyied; Isniyatin Faizah (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This research seeks to describe the presence of expert witnesses in the Egyptian court system. They are utilizing a literature study whose primary data comes from books, journals, reports, and laws. Then, the data is processed descriptively and analytically to explain the subject matter described. The results showed that expert witnesses, or in Egyptian terms referred to as Expert Witness Reports, are enshrined in the Egyptian Evidence Law, No. 25 of 1968, used in Egyptian courts to obtain specialized advice on specific legal issues. Legal regulations govern the procedure for selecting expert witnesses and require the court to appoint one or three experts who must meet specific criteria. The whole process of the expert report must be conducted within the courtroom. The rules regarding the presence of expert witnesses in Egyptian courts also underline the importance of expert witnesses in legal proceedings. The rules emphasize the efforts made to ensure transparency, accuracy, and excellence in expert witness reports, essential to facilitate dispute resolution in court. The government takes a role in this matter through payment facilities for expert witnesses, not all of which is borne by the parties to the dispute.